Analisis Pergerakan Harga Saham Garuda Sebelum Dan Sesudah Pemecatan Direktur Utama Garuda Oleh Mentri BUMN - Ratnawati Raflis (CV. ITTC INDONESIA, 2023)
The main purpose of this research is to find out the abnormal return (AR) of Garuda Indonesia shares and to find out the Trading Volume Activity (TVA) of Garuda Indonesia shares. This study uses an event study (event study). Event study is a study that studies the reaction of the capital market to an event whose information is published as an announcement, namely by analyzing changes in the object under study in connection with events that have occurred. Event studies can be used in several events such as elections, political unrest, terrorist attacks, wars, or corporate actions carried out by companies such as rights issues, stock splits, bonus shares, dividend distributions, initial public offerings, stock conversions and so on. shows that there is a difference in Trading Volume Activity between before and after. This is because the t-count value is 2.818 and the significance value (0.031) <0.05. then the second hypothesis Ho is rejected, Ha is accepted. This means that the higher the value of the previous Trading Volume Activity, the value of the Trading Volume Activity after that will not change